2006
DOI: 10.1002/jnr.21000
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of copper/zinc‐superoxide dismutase in transgenic mice markedly impairs regeneration and increases development of neuropathic pain after sciatic nerve injury

Abstract: Despite the general capacity of peripheral nervous system to regenerate, peripheral nerve injury is often followed by incomplete recovery of function, sometimes with the burden of neuropathic pain. The mechanisms of both regeneration and nociception have not been clarified, but it is known that inflammatory reactions are involved. Cu/Zn-superoxide dismutase (SOD1) is an important scavenger protein that acts against oxidative stress. It has been shown to play an important role in apoptosis and inflammation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…As a consequence of oxidative stress both the function and transport of mitochondrial to synaptic regions is impaired, decrease synaptic function [15,16], which results in neurodegeneration after brain injury [17,18]. A recent study reported that oxidative stress alters the function of PSD-95 by decreasing a voltage-gated potassium channel that is closely linked to the PSD [19], suggesting that synapse loss and replacement, known to occur following TBI [20], could be modulated by the levels of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of oxidative stress both the function and transport of mitochondrial to synaptic regions is impaired, decrease synaptic function [15,16], which results in neurodegeneration after brain injury [17,18]. A recent study reported that oxidative stress alters the function of PSD-95 by decreasing a voltage-gated potassium channel that is closely linked to the PSD [19], suggesting that synapse loss and replacement, known to occur following TBI [20], could be modulated by the levels of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] We have previously shown that following TBI there is a significant loss of synaptic proteins in both the cortex and hippocampus. 22,23 This synaptic change occurs much later than the increase in levels of oxidative stress, which is a very early and longlasting event.…”
mentioning
confidence: 99%
“…A study suggests that copper ions may inhibit neuron growth and repair, adversely impacting nerve regeneration ( Kotulska et al, 2006 ). Conversely, copper ions could have a beneficial effect on this process.…”
Section: Predictions Of Treatment On Stroke By Cuproptosismentioning
confidence: 99%